Cell-based assays for Parkinson’s disease using differentiated human LUHMES cells - ZHANG Xiao-min; YIN Ming; ZHANG Min-hua (Acta Pharmacologica Sinica, 2016)
Xiao-min ZHANG1, 2, Ming YIN1, Min-hua ZHANG2, * 1School of Pharmacy, Shanghai Jiao Tong University, Shanghai 200240, China; 2Neurodegeneration DPU, GlaxoSmithKline (China) R&D Company Limited, Shanghai 201203, China Aim: Lund human mesencephalic (LUHMES) cells can be differentiated to post-mitotic cells with biochemical, morphological and functional features of dopaminergic (DAergic) neurons. Given the limited scale of primary DAergic neuron culture, we developed differentiated LUHMES cell-based cytotoxicity assays for identifying neuroprotective agents for Parkinson’s disease (PD). Methods: LUHMES cells were incubated in a differentiation medium containing cAMP and GDNF for 6 d, and then differentiated cells were treated with MPP+ or infected with baculovirus containing α-synuclein. Cytotoxicity was determined by measuring intracellular ATP levels and caspase 3/7 activity in the cells. DAergic neuron-specific marker protein and mRNA levels in the cells were analyzed using Western blotting and RT-PCR, respectively. Results: LUHMES cells grew extensive neurites and became post-mitotic neuron-like cells during differentiation period, and three DAergic neuron markers TH, DAT and Nurr1 exhibited different expression profiles. MPP+ dose-dependently reduced ATP levels in the cells with an IC50 value of 65 μmol/L. MPP+ (80 μmol/L) significantly increased caspase 3/7 activity in the cells. Both the CDK inhibitor GW8510 and the GSK3β inhibitor SB216763 effectively rescued MPP+-induced reduction of ATP levels with EC50 values of 12 and 205 nmol/L, respectively. Overexpression of α-synuclein also significantly decreased intracellular ATP levels and increased caspase 3/7 activity in the cells. GW8510 and SB216763 effectively rescued α-synuclein overexpression-induced reduction of ATP levels, whereas GW8510, but not SB216763, ameliorated α-synuclein overexpression-induced increase of caspase 3/7 activity. Conclusion: MPP+- and α-synuclein overexpression-induced cytotoxicity of differentiated LUHMES cells may serve as good alternative systems for identifying neuroprotective compounds for PD. Keywords: LUHMES cell; dopaminergic neuron; cytotoxicity; MPP+; α-synuclein; GW8510; SB216763; cell-based assay; Parkinson’s disease * To whom correspondence should be addressed. E-mail Minhua.m.zhang@gsk.com Received 2013-11-19 Accepted 2014-03-25